2013
DOI: 10.1136/bcr-2013-009285
|View full text |Cite
|
Sign up to set email alerts
|

Spinal epidural abscess treated with antibiotics alone

Abstract: SUMMARYSpinal epidural abscess (SEA) is a rare clinical condition among children. Most patients do not present with classical signs. A 13-year-old boy without any predisposing factors presented with paraparesis, bladder and bowel involvement. MRI spine demonstrated an SEA at the C7 and D1 levels on both sides of the midline with cord oedema at the C2-3 to C6 level with minimal marrow oedema in the C6 vertebral body. We treated the patient with antibiotics (ceftriaxone and vancomycin) alone. The patient showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…All nine received 4–6 weeks of intravenous therapy, and all recovered without significant sequelae. Although some studies have described the successful use of antibiotic therapy alone in select patients, a combined surgical decompression and extended intravenous antibiotic therapy approach remains standard for paediatric patients' treatment …”
Section: Discussionmentioning
confidence: 99%
“…All nine received 4–6 weeks of intravenous therapy, and all recovered without significant sequelae. Although some studies have described the successful use of antibiotic therapy alone in select patients, a combined surgical decompression and extended intravenous antibiotic therapy approach remains standard for paediatric patients' treatment …”
Section: Discussionmentioning
confidence: 99%
“…It was reported that several causative organisms may cause SEA, including Staphylococcus aureus , Gram-negative bacteria, coagulase-negative bacteria, staphylococcus, Escherichia coli , Pseudomonas aeruginosa , streptococcus species, and Mycobacterium spp. [2,20,21] Among them, S. aureus is the leading agent. [22] Notably, the sensitivity of blood cultural test may decline with pre-use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…[21] MRI is crucial to establish the diagnosis and monitor the disease progression. [20,24] Especially, gadolinium-enhanced MRI is the most sensitive imaging method, [22] which should be taken as soon as SEA is suspected. [19] Relatively, CT scan is less specific and cannot distinguish SEA from other lesions that compress the thecal sac.…”
Section: Discussionmentioning
confidence: 99%
“…14 15 Spinal abscesses have been treated successfully with antibiotics alone or with image guided aspiration of the collection, although deterioration can be rapid and irreversible. 16 Some studies report a worse overall motor outcome in those treated conservatively, 14 except for spinal cord compression secondary to tuberculosis, which usually responds well to treatment with steroids and antibiotics. Severely debilitated patients might not be suitable for surgery if they are not fit for general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%